Hybrid organo-inorganic composite materials of incorporative type based on calcium phosphates for bone surgery - Krivileva, S.P.; Rassokha, O.M.; Zakovorotnyi, O.Yu.; Zinchenko, M.G.; Bukatenko, N.O.; Zhukov, V.I. (Functional Materials, 2018)
Proposed is a concept for the obtaining of a hybrid organo-inorganic composite material of incorporative type with a binder based on sevilen and an inorganic filler based on nanoparticles of Ca₃(PO₄)₂ nanoparticles. The binder simultaneously contains two different phases: α- and β-modifications of Ca₃(PO₄)₂ separated by a coherent boundary. It is shown that during the formation of the composite several processes occur simultaneously. They are: partial hydration of α-Ca₃(PO₄)₂, partial hydrolysis of sevilen, as well as intermolecular structuring due to the formation of chelate complexes. Studied is the effect of the composition, structure, the ratio of initial components on the properties of the composite.